Vertebral metastases from intracranial meningioma - Zaghouani, H (SAGE Publications, 2014)
Meningioma rarely gives rise to metastases outside the brain and meninges. We report here a case of a patient who was treated for anaplastic brain meningioma with surgery and fractionated radiation therapy without any recurrence until 5 years after the operation, when she developed vertebral metastases.